The paradoxes of sustainable HRM: Insights through the perspective of common good, green, social responsibility, and triple bottom line - Ahmad Hafizi, Ahmad Giran; Puteri Fadzline, Muhamad Tamyez; Muhammad Ashraf, Fauzi (SAGE Publications Ltd, 2025)
Background: With the increasing demand for sustainability in traditional human resource management (HRM), firms in developing countries struggle to meet both efficiency and sustainability needs. In response to this deficiency, the present study proposes a sustainable human resource management (SHRM) model focusing on the interaction of SHRM pillars with the perceived barriers and paradoxical views among human resource (HR) managers. Objective: This paper employs an exploratory qualitative case study of how SHRM is perceived from the perspective of HR managers and their paradoxical views and barriers during the process. Methods: Drawing on paradox theory and derive the data from four semi-structured interviews. The study engaged with a qualitative research tool using ATLAS.ti 24. Results: The study found that the four pillars of SHRM are dominantly present, namely, socially responsible human resource management, green human resource management, triple bottom line, and common good human resource management, while another pillar of SHRM, namely, triple bottom line found a weak balance between planet, profit, and people, which significantly shows an efficiency-substance paradox. Other paradoxes were identified, namely, the efficiency-responsibility paradox and the present-future paradox. Conclusions: We present an integrated model of interaction between pillars, barriers, and paradoxes of SHRM practices to guide HR managers in decision-making, planning, and evaluation. The study implies that although firms have demonstrated SHRM practices, external and internal support is certainly needed to fully assist them in managing SHRM and their paradoxical views and concerns.